Intracranial Hemorrhage due to Rupture of an Anterior Communicating Artery Aneurysm in a Patient With Pituitary Adenoma. Issue 2 (March 2015) - Tian, Xuping; Shu, Hansheng; Zhang, Hui; Wang, Hao; Guo, Liemei
<x xml:space="preserve">Abstract</x> Abstract The coexistence of pituitary adenoma (PA) and anterior communicating artery aneurysm is extremely rare, making the diagnosis difficult and the treatment challenging. Herein, we present a PA patient with intracranial hemorrhage due to rupture of an anterior communicating artery aneurysm. For the best diagnosis of intracranial aneurysm among PA patients, cranial magnetic resonancetogether with three-dimensional time-of-flight magnetic resonanceangiography are strongly recommended. Previous treatment ofthe intracranial aneurysm is advisable and essential to avoid possible catastrophic bleeding during the transsphenoidal or microsurgical removal of PA.